Circular RNAs: A Novel Player in Development and Disease of the Central Nervous System - Xie, Lili; Mao, Mao; Xiong, Kun; Jiang, Bing (Frontiers in Cellular Neuroscience, 2017)
Circular RNAs (circRNAs) own unique capabilities to communicate with nucleic acids and ribonucleoproteins and are emerging as indispensable compositions of the regulatory messages encoded in the genome. Due to lack of 3’ termini, circRNAs are more resistant to degradation by exonuclease RNase R and possess greater stability than linear RNAs. Moreover, circRNAs can act as microRNA (miRNA) sponge and affect messager RNA (mRNA) splicing and transcription. By virtue of their great stability and elaborate regulatory mechanisms of gene expression, circRNAs play important roles in certain physiological activities. The development, homeostasis and stress response of the central nervous system (CNS) depend upon precise temporal and spatial regulation of gene networks. Moreover, emerging evidence has revealed that circRNAs are spatiotemporally regulated and dynamically expressed during brain development; therefore, they can exert significant influences on CNS development and diseases. In this review, we highlight the biogenesis of circRNAs and their central roles in regulation of CNS development and diseases.